Subjective Well-Being Guru PAUD Non Sarjana di Desa Gunungsari Kecamatan Tlogowungu Kabupaten Pati - Fithriyatun, Fithriyatun (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2023)
Subjective well-being is a concept that refers to an individual's evaluation of their life as a whole, including happiness, life satisfaction, and happiness. PAUD (Early Childhood Education) teachers who do not have a bachelor's degree often face challenges and constraints in their profession. The aims of this study were: 1) To find out how the condition of the subjective welfare of non-graduate PAUD teachers in Gunungsari Village, Tlogowungu District, Pati Regency. 2) Exploring the factors of happiness and life satisfaction of non-graduate PAUD teachers in Gunungsari Village, Tlogowungu District, Pati Regency. The type of research that the authors use is phenomenological qualitative research. Phenomenology itself comes from the word phenomenon which means the appearance of an object, event or condition in the perception of an individual. Data collection techniques are through observation, interviews, and documentation while data analysis is data reduction, data presentation, verification, and drawing conclusions. The results of the study show that even though non-graduate PAUD teachers face obstacles such as the burden and patience required in dealing with children, they can still feel high subjective well-being. includes factors that contribute to the welfare of non-graduate PAUD teachers, factors of gratitude, personality, environment, economy, optimism.